Effect of Dietary Supplementation of Durvillaea Antarctica Meal on Production and Meat Quality Traits of Lambs - John Quiñones; Rodrigo Huaquipán; Rommy Díaz; Isabela Pérez Núñez; Matías Cortes; Ailín Martínez; Gastón Sepúlveda; Lidiana Velaszquez; David Cancino; Erwin Paz; Néstor Sepulveda (Animals)
Worldwide, there are reports indicating that sheep raised in insular systems spontaneously consume seaweed. In the southern hemisphere, there exists Durvillaea antarctica, a brown seaweed that possesses minerals and fatty acids that could improve some aspects of sheep production and meat quality, respectively. However, the consumption of this algae in lambs has been scarcely studied. The objective of this study was to evaluate the effects of dietary inclusion of Durvillaea antarctica meal on the growth performance, blood profile, and meat quality of fattening lambs. Thirty Araucana Creole lambs were housed and allocated to three pens. One pen served as a control, while the remaining two were supplemented with diets containing 5% and 10% Durvillaea antarctica meal. After 9 weeks, the animals were slaughtered. The dietary treatments did not significantly affect body weight and blood biochemical parameters. However, changes were observed in meat quality traits, including increased redness and reduced luminosity in the loin for the high inclusion treatment, in addition to slight alterations in pH and lower lipid oxidation in lambs’ meat fed Durvillaea antarctica. Furthermore, the meat from lambs supplemented with Durvillaea antarctica exhibited increased levels of linoleic acid and arachidonic acid, along with higher monounsaturated fatty acid content and a reduced omega-3/omega-6 ratio. This study shows that Durvillaea antarctica can be used to feed lambs without impairing growth or production parameters, which has been little studied. It is possible that this brown seaweed could be considered a natural additive to improve the quality and nutritional value of lamb meat. The effect of this seaweed on other ruminant models could be addressed in future studies.